Production of Reducing Sugar from Cassava Solid Waste by Simultaneous Ultrasonication and Acid Hydrolysis - Wasinton Simanjuntak; Heri Satria; Nurul Utami (Universitas Gadjah Mada, 2014)
In this study, acid hydrolysis of cassava solid waste under ultrasound irradiation for reducing sugar production was studied. A series of experiments was carried out under a 40 kHz ultrasound irradiation, with the main purpose to examine the effect of pHs, hydrolysis times, and temperatures on the concentration of reducing sugar produced. As a control an untreated sample was subjected to thermal hydrolysis under the optimum condition obtained from the hydrolysis experiments under ultrasound treatment. The results obtained indicated that the highest reducing sugar concentration was obtained from the experiment undertaken at pH = 2.0; hydrolysis time of 90 min, and temperature of 80 °C. Experiment conducted at this optimum condition was found to produce reducing sugar with the concentration of 801 mg/L. This concentration around 11 times over that produced from control sample, demonstrating that simultaneous ultrasonication and hydrolysis is far more effective than conventional thermal hydrolysis. This hydrolysis improvement is attributed to the ultrasound stimulated degradation of starch molecules, leading to accelerated hydrolysis due to the cavitations of the molecules, as evidently shown by the result of SEM characterization of the original and ultrasonicated sample.